Sustainable IFS at Landscape Level: Imperatives, Practices & Policy Options - Kumar, Shalander (International Crops Research Institute for the Semi-Arid Tropics, 2025)
In spite of successful pilot implementations of Integrated Farming Systems across diverse agro-ecological zones, large-scale adoption under smallholder systems remains limited due to resource optimization constraints, high transaction costs, knowledge-intensive requirements, and commodity-driven extension systems focused narrowly on seasonal crop planning. Smallholder systems in arid, semi-arid, and vulnerable regions are highly heterogeneous and significantly underperforming, with actions at the landscape scale having major implications for farming system outcomes. A systems science approach integrating multi-dimensional sustainability assessment, land resource inventory, hydrological assessments, and whole-farm bio-economic modeling offers promising pathways for transformation. A case study from Maharashtra reveals how integrated farm-to-landscape interventions transformed agricultural livelihoods through community-led approaches, resulting in enhanced water storage capacity, improved soil moisture, increased groundwater availability, conversion of fallow lands to double cropping, higher crop yields, and expanded livestock production. While the landscape approach significantly increased agro-biodiversity, it created new challenges around supply chain development for multiple commodities. Critical pathways forward include reorienting extension systems, developing landscape-level plans integrating resources and markets, establishing suitable business models for resource recycling and aggregation, and creating decision support tools for mainstreaming IFS concepts into agricultural development planning.